Strain improvement for cellulolytic enzymes for effective saccharification of lignocellulosic biomass by mutant of Penicillium funiculosum NCIM 1228 - Chavan, Sambhaji; Shete, Ashvini; Dharne, Mahesh S. (Systems Microbiology and Biomanufacturing, 2024)
Lignocellulosic biomass (LCB) generated from various agro-waste can be effectively used to manufacture a broad range of value-added products cost-effectively. However, the high cost of cellulases is still a major challenge in producing biofuels and biochemicals from LCB on an industrial scale. The enzyme output and activity of cellulase in the fermentation broth are closely linked in terms of enzyme manufacturing costs. Therefore, research on efficient fermentation processes of hyperactive fungi, and cost-effective recovery systems have been directed toward lowering enzyme costs and increasing overall enzyme production. Penicillium funiculosum NCIM 1228 (P. funiculosum NCIM 1228) is a feasible cellulase-producing strain that possesses all four enzymes required to efficiently hydrolyse LCB. The primary objective of this study was to employ random mutagenesis to increase enzymes titer, yield, and productivity. The potential mutant D4 (derived by Ethyl methanesulfonate (EMS) mutation) exhibited 6.47, 3.05, 3.03, and 3.19-fold higher activities of FPase, CMCase, β-glucosidase, and xylanase, respectively, compared to the parent strain. Mutant D4 demonstrated a promising protein titer of 17.96 g/L at the 40 L fermenter scale, with productivities of 479, 4249, and 6987 U/L/day for FPase, CMCase, and Xylanase, respectively, on the tenth day. Interestingly, the crude form of enzymes from the mutant demonstrated promising saccharification, releasing 3.54% of glucose and achieving a 54.03% of cellulose conversion efficiency without formulation. In comparison, a commercially formulated enzyme exhibited 53.07% efficiency against pre-treated sugarcane bagasse, indicating its promising potential for future applications.